Pemetaan Masyarakat Pendonor Darah Berbasis WebGIS di Kota Metro - Miristika Alliyu; Ilyas; Nurhayati, Misfallah; Ramadhini, Meraty; Aulia, Rizqi (LPPM Politeknik Aceh Selatan, 2025)
The availability of sufficient blood supplies is essential for fulfilling medical requirements, particularly in emergency scenarios. In Indonesia, the Indonesian Red Cross (Palang Merah Indonesia, PMI) is tasked with managing blood supplies across various regions, including Metro City. However, the current donor data management system at PMI Metro City is not yet fully optimized, potentially undermining efforts to meet local blood demands. Inconsistent donor data management poses significant challenges to blood transfusion processes, especially during emergencies. To address these inefficiencies, this study aims to develop a database system integrated with a Web-based Geographic Information System (WebGIS). The proposed WebGIS platform provides an interactive and informative visualization of blood donor distribution across Metro City. The system development follows a structured methodology comprising several phases: planning, data identification, WebGIS development using PHP, HTML, CSS, JavaScript, and Leaflet, and web hosting. The key outcomes of this research include a well-structured database and an interactive web-based map for identifying donor locations. The WebGIS system enhances PMI’s capacity to optimize blood supply strategies, particularly for urgent medical needs, by improving real-time visibility and management of donor data.